2007
DOI: 10.1143/jjap.46.7089
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Piezoelectric (Li,Na,K)NbO3 Porous Ceramics and (Li,Na,K)NbO3/KNbO3 Composites

Abstract: Porous Li 0:06 (Na 0:5 K 0:5 ) 0:94 NbO 3 (LNKN-6) ceramics with different pore volumes have been prepared using preceramic powder and phenol resin fiber (KynolÔ) as a pore former. It was confirmed that the porous ceramics synthesized by the ''twostage firing method'' suppressed the loss of alkali elements from the porous body during heat treatment. The porous LNKN-6 ceramics were then converted to LNKN-6/KNbO 3 composites through soaking and heat treatment using a sol-gel precursor source composed of KNbO 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Gold electrodes were formed on both surfaces by sputtering, and the samples were heated at 300°C for 10 min to improve the adhesion. The samples were sawed into a size of 4 © 1.5 © 0.4 mm 3 . The room temperature dielectric constant and loss were measured at frequencies from 40 Hz to 1 MHz using an impedance analyzer (HP4294A, Agilent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold electrodes were formed on both surfaces by sputtering, and the samples were heated at 300°C for 10 min to improve the adhesion. The samples were sawed into a size of 4 © 1.5 © 0.4 mm 3 . The room temperature dielectric constant and loss were measured at frequencies from 40 Hz to 1 MHz using an impedance analyzer (HP4294A, Agilent).…”
Section: Methodsmentioning
confidence: 99%
“…15) The motion of the fine domains by the electric field was observed, which was suggested to lead the large piezoelectric properties. 16) Since nano-sized domains are also reported for solid-solutions of relaxors Pb(Zn 1/3 Nb 2/3 )O 3 and Pb(Mg 1/3 Nb 2/3 )O 3 and ferroelectric PbTiO 3 with large piezoelectric properties, 17),18) they may be associated with the increased piezoelectric response of PZT at MPB.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, they are not shown in this paper. In fact, Hikita [17] and Kakimoto [19] reported opposite results about the piezoelectric constant (d 33 ) in relation to the porosity. Hikita [17] found that d 33 slightly increases with the porosity content while Kakimoto [19] found that d 33 decreases with the porosity content.…”
Section: Piezoelectric Propertiesmentioning
confidence: 94%
“…In fact, Hikita [17] and Kakimoto [19] reported opposite results about the piezoelectric constant (d 33 ) in relation to the porosity. Hikita [17] found that d 33 slightly increases with the porosity content while Kakimoto [19] found that d 33 decreases with the porosity content. As a result, the big difference of d 33 and 33 / o for the two hipped samples may belong to one or two of the following reasons: the relative density difference and unsaturated polarization.…”
Section: Piezoelectric Propertiesmentioning
confidence: 94%
“…The values obtained for dense PZT reference samples were d bulk 33 ¼ 325 pCN À1 , d bulk 31 ¼À140 pCN À1 , and relative permittivity e bulk r ¼ 1195 [25] and for dense LNKN-six reference samples were d bulk 33 ¼ 195 pCN À1 , d bulk 31 ¼-7.36 pCN À1 , and relative permittivity e bulk r ¼ 740, [26] respectively. Polarization was carried out with 3 kV mm À1 at 150 C (PZT) and at 80 C (LNKN-6) in a silicone oil bath for 1 h. The relative permittivity e r and the longitudinal piezoelectric coefficients d 33 and d 31 were measured by Berlincount method (Piezo-Meter PM 300, Piezo Test, London, England).…”
Section: Methodsmentioning
confidence: 99%